ANALYSIS OF THE MARKET LEADERSHIP ORIENTATION, INNOVATION STRATEGY AND BUSINESS PERFORMANCE - Setiarini Setiarini; Sri Irviati Wahyoeni; Iha Haryani Hatta; Widarto Rachbini (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2020)
The Small Medium Enterprise (SME) Indonesia is able to absorb the largest of labor, therefore needs to support continuation through the achievement of optimal business performance. The Purpose of Research Analysis Market Orientation Leadership, Innovation Strategy and Business Performance (Study case SME in Jakata) has analysis the variable influence among of Market Orientation Leadership, Innovation Strategy and Business Performance. The population of this research are home industry SME in Jakarta, Data collection through surveys with respondents re-elected as many as 162 purposive perpetrators of SME. The respondent’s data has analyzed in Structural Equation Modeling (SEM), Lisrel’s program. The results of the study as follows: The market orientation leadership influence to Innovation Strategy. The Variables of market orientation leadership and innovation strategy influence partial to business performance. The Innovation Strategy as the intervening as variables on the orientation market leadership and business performance variables.